The effect of Telehealth Antimicrobial Stewardship Program (Tele-ASP) on antimicrobial use in a pediatric intensive care unit: Pre- and post-implementation single center study - Abdulla Alfraij; Ahmed Abdelmoniem; Mohamed Elseadawy; Mohammad Surour; Mohamed Basuni; Jesse Papenburg; Mohammad Alghounaim (Journal of Infection and Public Health, 2023)
Background: Overuse or misuse of antimicrobials is common in pediatric intensive care units (PICU) and may be associated with poor clinical outcomes. Although an antimicrobial stewardship program (ASP) has been found to improve this practice, the required expertise in infectious diseases may be limited in some centers. We aimed to evaluate the effect of telehealth ASP on the rate of PICU antimicrobial use in a center without a local Infectious Diseases consultation service. Methods: A retrospective cohort study was performed between October 1st, 2018, and October 31st, 2020, in Farwaniya Hospital PICU, a 20-bed unit. All pediatric patients who were admitted to PICU and received systemic antimicrobials during the study period were included and followed until hospital discharge. The ASP team provided weekly prospective audit and feedback on antimicrobial use starting October 8th, 2019. A pediatric infectious diseases specialist joined the ASP rounds remotely. Descriptive analyses and a pre-post intervention comparison of days of therapy (DOT) were used to assess the effectiveness of the ASP intervention. Results: There were 272 and 156 PICU admissions received systemic antimicrobial before and after the initiation of ASP, respectively. Bronchiolitis and pneumonia were the most common admission diagnoses, together compromising 60.7% and 61.2% of cases pre- and post-ASP. The requirement for respiratory support was higher post-ASP (76.5% vs. 91.5%, p < 0.001). Average monthly antimicrobial use decreased from 922 (95%CI 745–1000) to 485 DOT/1000 patient-days (95%CI 246–722, P < 0.05). A decline in DOT was observed across most antibiotic classes, except for ceftriaxone. No effect on the length of PICU stay, length of hospitalization, or mortality was observed. Most (89.7%) ASP recommendations were followed either fully or partially. Conclusion: In settings where Infectious Diseases consultation services are unavailable, PICU telehealth ASP can be effectively implemented and associated with significantly reducing antimicrobial use.